Assessment of measurement precision in single‐voxel spectroscopy at 7 T: Toward minimal detectable changes of metabolite concentrations in the human brain in vivo. Issue 3 (16th November 2021) - Riemann, Layla Tabea; Aigner, Christoph Stefan; Ellison, Stephen L. R.; Brühl, Rüdiger; Mekle, Ralf; Schmitter, Sebastian; Speck, Oliver; Rose, Georg; Ittermann, Bernd; Fillmer, Ariane
Abstract : Purpose: To introduce a study design and statistical analysis framework to assess the repeatability, reproducibility, and minimal detectable changes (MDCs) of metabolite concentrations determined by in vivo MRS. Methods: An unbalanced nested study design was chosen to acquire in vivo MRS data within different repeatability and reproducibility scenarios. A spin‐echo, full‐intensity acquired localized (SPECIAL) sequence was employed at 7 T utlizing three different inversion pulses: a hyperbolic secant (HS), a gradient offset independent adiabaticity (GOIA), and a wideband, uniform rate, smooth truncation (WURST) pulse. Metabolite concentrations, Cramér‐Rao lower bounds (CRLBs) and coefficients of variation (CVs) were calculated. Both Bland‐Altman analysis and a restricted maximum‐likelihood estimation (REML) analysis were performed to estimate the different variance contributions of the repeatability and reproducibility of the measured concentration. A Bland‐Altmann analysis of the spectral shape was performed to assess the variance of the spectral shape, independent of quantification model influences. Results: For the used setup, minimal detectable changes of brain metabolite concentrations were found to be between 0.40 µmol/g and 2.23 µmol/g. CRLBs account for only 16 % to 74 % of the total variance of the metabolite concentrations. The application of gradient‐modulated inversion pulses in SPECIAL led to slightly improved repeatability, but overall reproducibility appeared to be limited by differences in positioning, calibration, and other day‐to‐day variations throughout different sessions. Conclusion: A framework is introduced to estimate the precision of metabolite concentrations obtained by MRS in vivo, and the minimal detectable changes for 13 metabolite concentrations measured at 7 T using SPECIAL are obtained.